2019
DOI: 10.1055/a-0835-5940
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic management of biliary leaks: a systematic review with meta-analysis

Abstract: Background The first-line approach to the treatment of biliary leaks is endoscopic retrograde cholangiopancreatography. A variety of techniques can be used, including sphincterotomy, stenting, a combination of both techniques, or nasobiliary drainage. We performed a systematic review with meta-analysis to define the optimal strategy. Methods We searched MEDLINE/PubMed, EMBASE, CENTRAL, Scopus, Google Scholar, and Web of Science until January 2018 for randomized clinical trials, case-control studies, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0
10

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(31 citation statements)
references
References 32 publications
0
21
0
10
Order By: Relevance
“…Techniques that are commonly used include bile duct sphincterotomy, bile duct stenting, or a combination of both [2,3]. Recent studies have evaluated the clinical efficacy and outcomes of these techniques, but the results have been varied and controversial [4][5][6].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Techniques that are commonly used include bile duct sphincterotomy, bile duct stenting, or a combination of both [2,3]. Recent studies have evaluated the clinical efficacy and outcomes of these techniques, but the results have been varied and controversial [4][5][6].…”
Section: Methodsmentioning
confidence: 99%
“…Explorys is a Health Insurance Portability and Accountability Act (HIPAA)-and Health Information Technology for Economic and Clinical Health Act (HITECH)-compliant platform, and institutional review board approval for its use is not required. This study was reported according to the Strengthening the Reporting of Observational Studies in Epidemiology (STROBE) guidelines for observational cohort studies [2].…”
Section: Databasementioning
confidence: 99%
“…The goal of the endoscopic treatment is to eliminate the transpapillary pressure by performing a sphincterotomy, placing a biliary stent or the combination of both, lowering the pressure on the bile duct which allows healing the leak (1,3) . Large and refractory bile leaks are often treated with multiple plastic stents or self-expandable metal stents (SEMS), and usually stents are removed after 4 to 8 weeks (2) . The aims of this study are to determine efficacy of endoscopic treatment of bile leaks secondary to cholecystectomy, hepatectomies, and hepatic trauma and to compare the currently employed ERCP approaches to biliary leaks: endoscopic sphincterotomy alone and sphincterotomy plus biliary stenting, regarding the number of days needed to remove the abdominal surgical drain or cessation of drainage after each technique.…”
Section: Endoscopic Retrograde Cholangiopancreatography (Ercp)mentioning
confidence: 99%
“…Bile leaks are a potentially serious complication that can occur after cholecystectomy, liver transplantation, partial hepatectomy, and hepatic damage secondary to abdominal trauma (1,2) . Although post cholecystectomy surgery is responsible for most of biliary injuries, it occurs with an incidence of only 1% (3,4) .…”
Section: Introductionmentioning
confidence: 99%
“…5 A systematic review has reported the success rate of endoscopic therapy for bile leak to be 68% to 98.3%. 6 The current proposed treatment algorithm for bile leak is shown in Fig. 1.…”
mentioning
confidence: 99%